LINC00958 promotes proliferation, migration, invasion, and epithelial-mesenchymal transition of oesophageal squamous cell carcinoma cells. - Biqi Wang; Duo Tang; Zijia Liu; Qian Wang; Shan Xue; Zijie Zhao; Dongdong Feng; Chao Sheng; Jintao Li; Zhixiang Zhou (PLoS ONE)
Oesophageal cancer is one of the deadliest cancers in the world. Oesophageal squamous cell carcinoma (ESCC) is the most prevalent histological type of oesophageal cancer. Oesophageal cancer has a poor prognosis because of its invasiveness. Thus, it is especially important to seek effective treatment methods. Research indicates that long non-coding RNAs (lncRNAs) play a significant role in the occurrence and development of oesophageal cancer. The aim of this study was to describe the role of LINC00958 in ESCC. Bioinformatics and real-time quantitative polymerase chain reaction (RT-qPCR) methods were utilized to predict and verify the expression of LINC00958 in ESCC. Related functional experiments, including cell proliferation, migration and invasion, were performed. In addition, a western blot and a dual luciferase reporter gene experiment were used to study the detailed carcinogenic mechanism of LINC00958. The results indicated there was a high expression of LINC00958 in ESCC, which promoted proliferation, migration, invasion and Epithelial-Mesenchymal Transition (EMT) of ESCC cells, and this effect may be via regulating miR-510-5p.